Development of the Board Game "Petualangan Si Kelinci Kecil" as a Tool for Early Childhood Literacy Stimulation in Raudhatul Athfal Istiqlal Jakarta - Dewi, Tammy Sri Utami; Imamah (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study develops and evaluates "The Adventure of the Little Rabbit," an interactive board game designed to enhance early childhood literacy. Using the ADDIE model within a Research and Development (R&D) approach, the game was tested with 30 children and 2 teachers at RA Istiqlal Jakarta. Expert validation confirmed its educational value, clarity, and design suitability, with feasibility scores ranging from 75.5% to 81%. A pre-test and post-test showed significant improvements in letter recognition, phonemic awareness, word formation, and writing skills. Observations and teacher feedback highlighted high engagement and motivation among children. The results indicate that the board game is an effective and engaging tool for literacy development. Future research should explore its long-term impact and broader applications.